Lignin Dimers as Potential Markers for 14C-young Terrestrial Dissolved Organic Matter in the Critical Zone - Benk, Simon A.; Li, Yan; Roth, Vanessa-Nina; Gleixner, Gerd (Frontiers in Earth Science, 2018)
The origin, molecular composition and fate of dissolved organic matter (DOM) provides essential information that links surface and subsurface processes and explores the functioning of the Critical Zone. Therefore it is important to identify specific marker compounds that provide information on the temporal and spatial linkages in the Critical Zone. Here we used ultra-high resolution mass spectrometry and accelerator mass spectrometry in order to identify markers for fast transport of surface-derived DOM through the Critical Zone. We assessed the molecular composition and radiocarbon age of solid phase extracted DOM (SPE-DOM) from forest top soils. The 14C ages of SPE-DOM in our study were similar to that of bulk DOM. Calibrated ages ranged from 0 to 49 years and the within-site variability was larger than between sampling sites. Spearman rank correlation between the 14C ages and the DOM composition identified 129 sum formulae that were significantly correlated to 14C age. We found that molecular entities with younger 14C ages had lower molecular weight, higher unsaturation and less oxygen and heteroatoms than those associated with older 14C ages. A chemical library search suggested that phenylpropanoids and compounds, which are known to be lignin derived, are key molecular species for terrestrial DOM with young 14C ages. Among them, lignin dimers emerged as prominent surface-derived compounds that can potentially be used as markers for fast transport of water and DOM into the subsurface and groundwater.